Controlling the dimensionality of on-surface coordination polymers via endo- or exoligation - Shchyrba, Aneliia; Gade, Lutz H. (Journal of the American Chemical Society, 2014)
The formation of on-surface coordination polymers is controlled by the interplay of chemical reactivity and structure of the building blocks, as well as by the orientating role of the substrate registry. Beyond the predetermined patterns of structural assembly, the chemical reactivity of the reactants involved may provide alternative pathways in their aggregation. Organic molecules, which are transformed in a surface reaction, may be subsequently trapped via coordination of homo- or heterometal adatoms, which may also play a role in the molecular transformation. The amino-functionalized perylene derivative, 4,9-diaminoperylene quinone-3,10-diimine (DPDI), undergoes specific levels of dehydrogenation (−1 H2 or −3 H2) depending on the nature of the present adatoms (Fe, Co, Ni or Cu). In this way, the molecule is converted to an endo- or an exoligand, possessing a concave or convex arrangement of ligating atoms, which is decisive for the formation of either 1D or 2D coordination polymers.
Gesehen am 07.08.2020